2016
DOI: 10.1001/jamaophthalmol.2015.4518
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Nerve Regeneration After Collagen Cross-Linking Treatment of Keratoconus

Abstract: IMPORTANCE It is unknown whether a neurotrophic deficit or pathologic nerve morphology persists in keratoconus in the long term after corneal collagen cross-linking (CXL) treatment. Nerve pathology could impact long-term corneal status in patients with keratoconus. OBJECTIVE To determine whether CXL treatment of keratoconus results in normalization of subbasal nerve density and architecture up to 5 years after treatment. DESIGN, SETTING, AND PARTICIPANTS Observational study of 19 patients with early-stage kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…It should be mentioned that none of the patients in our study developed severe dry eye after the surgery, even though there are studies [18] that indicate abnormal corneal innervation and dry eye after collagen crosslinking.…”
Section: Discussionmentioning
confidence: 59%
“…It should be mentioned that none of the patients in our study developed severe dry eye after the surgery, even though there are studies [18] that indicate abnormal corneal innervation and dry eye after collagen crosslinking.…”
Section: Discussionmentioning
confidence: 59%
“…We found that the nerve fibers had a thickened, prominent appearance, such as excessive branching and curling, and were even interrupted, which may be attributable to alterations in the corneal biomechanics in keratoconus, such as folds and rupturing of the stromal lamellae. Parissi et al [ 23 ] reported that keratoconus was characterized by a progressive decreasing nerve density and altered nerve morphology, despite CXL treatment. In addition, it was reported that the anterior collagen lamellae were disturbed as observed by histopathology and X-ray scattering techniques [ 4 , 17 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60][61][62][63] An initial decrease in nerve density was observed after SMILE Xtra on confocal microscopy, 39 characterized by disappearance of some of the subepithelial nerve fibres from the central treated area for up to 3 months after treatment. [57][58][59][60][61][62][63] An initial decrease in nerve density was observed after SMILE Xtra on confocal microscopy, 39 characterized by disappearance of some of the subepithelial nerve fibres from the central treated area for up to 3 months after treatment.…”
Section: Change In Corneal Nervesmentioning
confidence: 99%
“…Corneal refractive surgery and UVA irradiation might have an effect on corneal nerves. [57][58][59][60][61][62][63] An initial decrease in nerve density was observed after SMILE Xtra on confocal microscopy, 39 characterized by disappearance of some of the subepithelial nerve fibres from the central treated area for up to 3 months after treatment. Regeneration of nerve fibres was characterized by subepithelial neuritic flocculations in the central irradiated area under the Bowman lamina at a depth of 50 μm at 3 months.…”
Section: Change In Corneal Nervesmentioning
confidence: 99%